Tibetan Medicine Qishiwei Zhenzhu Pills Can Reduce Cerebral Ischemia-Reperfusion Injury by Regulating Gut Microbiota and Inhibiting Inflammation. (11th November 2021) - Fu, Ke; Zhang, Dewei; Song, Yinglian; Xu, Min; Wu, Ruixia; Xiong, Xueqing; Liu, Xianwu; Wu, Lei; Guo, Ya; Zhou, You; Li, Xiaoli; Wang, Zhang
Abstract : Cerebral ischemia is a series of harmful reactions, such as acute necrosis of tissue, inflammation, apoptosis, autophagy, and blood-brain barrier injury, due to the insufficient blood supply to the brain. Inflammatory response and gut microbiota imbalance are important concomitant factors of cerebral ischemia and may increase the severity of cerebral ischemia through the gut-brain axis. Qishiwei Zhenzhu pills (QSW) contain more than 70 kinds of medicinal materials, which have the effects of anti-cerebral infarction, anti-convulsion, anti-dementia, and so on. It is a treasure of Tibetan medicine commonly used in the treatment of cerebral ischemia in Tibetan areas. In this study, we gave rats QSW (66.68 mg/kg) once by gavage in advance and then immediately established the rat middle cerebral artery occlusion (MCAO) model. After 24 hours of treatment, the neuroprotection, intestinal pathology, and gut microbiota were examined. The results showed that QSW could significantly reduce the neurobehavioral abnormalities and cerebral infarction rate in MCAO rats. Furthermore, qPCR, western blot, and immunohistochemistry results showed that QSW could effectively inhibit IL-6, IL-1 β, and other inflammatory factors so as to effectively reduce the inflammatory response of MCAO rats. Furthermore, QSW could improve intestinal integrity and reduce intestinal injury. 16S rRNA sequencing showed that QSW could significantly improve the gut microbiota disorder of MCAO rats. Specifically, at the phylum level, it can regulate the abundance of Firmicutes and Proteobacteria in the gut microbiota of rats with MCAO. At the genus level, it can adjust the abundance of Escherichia and Shigella . At the species level, it can adjust the abundance of Lactobacillus johnsonii and Lactobacillus reuteri . All in all, this study is the first to show that QSW can reduce the severity of cerebral ischemia-reperfusion injury by regulating gut microbiota and inhibiting the inflammatory response.